Small-pelagic Small-pelagic fisheries management strategic using ecosystem approach at Belu Regency, East Nusa Tenggara - Beatrix Maureen Rehatta; Mohammad Mukhlis Kamal; Mennofatria Boer; Achmad Fahrudin; Zairion (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2020)
Study on small-pelagic fisheries in the border regions between Indonesia - Timor Leste has taken place in Belu District, East Nusa Tenggara. It was aimed to assess the status of small pelagic management and formulate the strategic and tactical steps for implementing sustainable fisheries management. The study site took place at four villages at the sub-district of Tasifeto Timur and Kakuluk Mesak. Data were collected through interview techniques, observation, and measurement of 30 indicators from six domains of EAFM, ecosystem approach to fisheries management, of which assessment of each indicator within each domain was conducted and presented into the flag model. Based on that results, tactical decisions and strategic planning were formulated. The results showed that small-pelagic fisheries management in Belu classified as a fairly medium category. Domain fish resources and fishing technology classified as a good category and domain habitat and ecosystem, social, economic and institution are classified as a medium category. To improve small-pelagic fisheries management in Belu District, several indicators are recommended for improvement in form of tactical and strategic management decisions